Răspuns :
7-[5200:13-5*(360-2x]:20=2
5200:13-5*(360-2x]:20= 7-2
400-5×(360-2X) = 5×20
400-5×(360-2X) = 100
5×(360-2X) = 400-100
5×(360-2X) = 300
360-2X = 300:5
360-2X = 60
2X = 360-60
2X = 300
X = 300:2
X = 150
7-[5200:13-5×(360-2x)]:20=2
-[400-5×(360-2x)]:20=2-7
[400-5×(360-2x)]:20=5
400-5×(360-2x)=5×20
-5×(360-2x)=100-400
5×(360-2x)=300
360-2x=300:5
360-2x=60
2x=360-60
2x=300
x=300:2
x=150
-[400-5×(360-2x)]:20=2-7
[400-5×(360-2x)]:20=5
400-5×(360-2x)=5×20
-5×(360-2x)=100-400
5×(360-2x)=300
360-2x=300:5
360-2x=60
2x=360-60
2x=300
x=300:2
x=150